A call for innovative social media research in the field of augmentative and alternative communication. (2nd January 2017) - Hemsley, Bronwyn; Balandin, Susan; Palmer, Stuart; Dann, Stephen
Abstract: Augmentative and alternative communication (AAC) social media research is relatively new, and is built on a foundation of research on use of the Internet and social media by people with communication disabilities. Although the field is expanding to include a range of people who use AAC, there are limitations and gaps in research that will need to be addressed in order to keep pace with the rapid evolution of social media connectivity in assistive communication technologies. In this paper, we consider the aims, scope, and methodologies of AAC social media research, with a focus on social network sites. Lack of detailed attention to specific social network sites and little use of social media data limits the extent to which findings can be confirmed. Increased use of social media data across a range of platforms, including Instagram and YouTube, would provide important insights into the lives of people who use AAC and the ways in which they and their supporters use social media. New directions for AAC social media research are presented in line with those discussed at the social media research symposium at the International Society for Augmentative and Alternative Communication in Toronto, Canada, on August 12, 2016.